Anti‐PrPC antibody rescues cognition and synapses in transgenic alzheimer mice. Issue 3 (27th February 2019) - Cox, Timothy O.; Gunther, Erik C.; Brody, A. Harrison; Chiasseu, Marius T.; Stoner, Austin; Smith, Levi M.; Haas, Laura T.; Hammersley, Jayne; Rees, Gareth; Dosanjh, Bhupinder; Groves, Maria; Gardener, Matthew; et al.
Abstract: Objective: Amyloid‐beta oligomers (Aßo) trigger the development of Alzheimer's disease (AD) pathophysiology. Cellular prion protein (PrPC) initiates synaptic damage as a high affinity receptor for Aßo. Here, we evaluated the preclinical therapeutic efficacy of a fully human monoclonal antibody against PrPC. This AZ59 antibody selectively targets the Aβo binding site in the amino‐terminal unstructured domain of PrPC to avoid any potential risk of direct toxicity. Methods: Potency of AZ59 was evaluated by binding to PrPC, blockade of Aβo interaction and interruption of Aβo signaling. AZ59 was administered to mice by weekly intraperitoneal dosing and brain antibody measured. APP/PS1 transgenic mice were treated with AZ59 and assessed by memory tests, by brain biochemistry and by histochemistry for Aß, gliosis and synaptic density. Results: AZ59 binds PrPC with 100 pmol/L affinity and blocks human brain Aßo binding to PrPC, as well as prevents synaptotoxic signaling. Weekly i.p. dosing of 20 mg/kg AZ59 in a murine form achieves trough brain antibody levels greater than 10 nmol/L. Aged symptomatic APP/PS1 transgenic mice treated with AZ59 for 5–7 weeks show a full rescue of behavioral and synaptic loss phenotypes. This recovery occurs without clearance of plaque pathology or elimination of gliosis. AZ59 treatment also normalizes synaptic signaling abnormalities in transgenic brain. These benefits are dose‐dependent and persist for at least 1 month after the last dose. Interpretation: Preclinical data demonstrate that systemic AZ59 therapy rescues central synapses and memory function from transgenic Alzheimer's disease pathology, supporting a disease‐modifying therapeutic potential.